2006
DOI: 10.1159/000096920
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent Flexural Exanthema (SDRIFE or Baboon Syndrome) after Administration of Two Different Iodinated Radio Contrast Media

Abstract: In 1984, the baboon syndrome was described as a particular form of systemic contact dermatitis that occurred after the administration of a contact allergen in individuals previously sensitized by topical exposure to the same allergen. Its clinical picture presents as an erythema of the buttocks and upper inner thighs resembling the red bottom of baboons. This specific reaction was originally observed with mercury, nickel and ampicillin. Since then over 100 cases have been described, most of them without known … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
46
0
4

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(50 citation statements)
references
References 36 publications
0
46
0
4
Order By: Relevance
“…the symmetrical intertriginous and flexural involvement of the exanthema. SDRIFE, unlike BS, is a neutral term that avoids ethically and culturally offensive comparisons with an animal and, most importantly, identifies a relatively benign particular type of drug eruption, facilitating the diagnosis, prognosis and management of individual patients [10] . We believe this acronym is a useful addition to the existing terms.…”
mentioning
confidence: 99%
“…the symmetrical intertriginous and flexural involvement of the exanthema. SDRIFE, unlike BS, is a neutral term that avoids ethically and culturally offensive comparisons with an animal and, most importantly, identifies a relatively benign particular type of drug eruption, facilitating the diagnosis, prognosis and management of individual patients [10] . We believe this acronym is a useful addition to the existing terms.…”
mentioning
confidence: 99%
“…Amoxicillin is the most common drug causing SDRIFE, followed by cephalosporins, mitomycin C and radio contrast media [4]. We report herein a first case of acyclovir- and valacyclovir-induced SDRIFE, which was confirmed by an oral provocation test.…”
Section: Introductionmentioning
confidence: 70%
“…We congratulate Arnold et al [1] for their interesting report on symmetrical drug-related intertriginous and flexural exanthema (SDRIFE, baboon syndrome). We especially commend the first criterion of this syndrome stating, what we emphasized some 15 years ago [2] , that SDRIFE should be distinguished from hematogenous or systemic contact-type dermatitis, as suggested by Andersen et al [3] , when they first reported this syndrome.…”
mentioning
confidence: 89%
“…Second, the fifth criterion of SDRIFE is absence of systemic symptoms and signs, which according to the authors [1] is important to distinguish SDRIFE from drug rash with eosinophilia and systemic symptoms (DRESS). Here, we disagree.…”
mentioning
confidence: 99%